"Greater than the Sum of its Parts:" Coordinating Centers as Facilitators of Network-Level Work in Cancer Epidemiology Coordinating Center Enabled Networks - Rolland, Betsy (My University, 2013)
As collaborative research has increased in size and scope, the overhead of managing such large endeavors has also increased. In cancer epidemiology, one tool used to address the challenges of working on multi-institutional research projects is the employment of a Coordinating Center (CC) charged with the facilitation of the project's scientific objectives. Yet little research has been done on how CCs work or how their work affects the work of the networks in which they are employed, here called "Coordinating Center Enabled Networks," or CCENs. This study addresses the research question, How do CCs facilitate the network-level work of CCENs? Employing ethnographic methods and qualitative data analysis, this study incorporates seven months of observation and 9 interviews of CC staff and Principal Investigators, as well as 8 interviews with funding agency representatives and CCEN collaborators. This dissertation presents a definition of the CCEN form, describes the work of the CCEN and develops a typology of work practices, providing an analytical lens through which it is possible to get a better sense of precisely what a CCEN is and does. Finally, this study proposes a definition of facilitation in collaborative cancer epidemiology as the application of the CC's collective and individual knowledge and experience, amassed over years of experience supporting collaborative, multi-institutional research projects, to the development of systems and processes to address the challenges of networked science. This study highlights the need for more research in the area of coordination of collaborative work and the use of CCs in collaborative scientific research.
Thesis (Ph.D.)--University of Washington, 2013
Keywords: Collaboration; Computer Supported Cooperative Work; Coordinating Centers; Coordination; Studies of Science; Team Science; Social research; Epidemiology; human centered design and engineering